1993
DOI: 10.1021/jm00059a007
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly modified 2'-deoxy-2'-fluoro-phosphorothioate oligonucleotides as nuclease-resistant antisense compounds with high affinity and specificity for RNA targets

Abstract: "Uniformly" modified phosphodiester or phosphorothioate oligonucleotides incorporating 2'-deoxy-2'-fluoroadenosine, -guanosine, -uridine, and -cytidine, reported herein for the first time, when hybridized with RNA afforded consistent additive enhancement of duplex stability without compromising base-pair specificity. CD spectra of the 2'-deoxy-2'-fluoro-modified oligonucleotides hybridized with RNA indicated that the duplex adopts a fully A-form conformation. The 2'-deoxy-2'-fluoro-modified oligonucleotides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
238
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 405 publications
(249 citation statements)
references
References 26 publications
(65 reference statements)
5
238
0
Order By: Relevance
“…the puckering of the branched-chain 5' sugars (rI(2`OH)SdT and rT(2 OMe)sdT) exceeds the 3'-endo distribution of the ribonucleosides, and by far that of 2'-deoxynucleosides, a property that makes them more 'compatible binders' of targeted RNA (31). Cook and co-workers have also suggested that increased affinity of an antisense oligomer for a complementary RNA target can be achieved by decreasing the entropic motion of the sugar while mantaining a preorganized structure with an RNA-like conformation (21,32). The second factor is base sequence.…”
Section: Resultsmentioning
confidence: 99%
“…the puckering of the branched-chain 5' sugars (rI(2`OH)SdT and rT(2 OMe)sdT) exceeds the 3'-endo distribution of the ribonucleosides, and by far that of 2'-deoxynucleosides, a property that makes them more 'compatible binders' of targeted RNA (31). Cook and co-workers have also suggested that increased affinity of an antisense oligomer for a complementary RNA target can be achieved by decreasing the entropic motion of the sugar while mantaining a preorganized structure with an RNA-like conformation (21,32). The second factor is base sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The 2′-position of the sugar moiety can also serve as a modification site. 2′-methoxy (2′-O-methyl) substituted oligonucleotides were found to form very stable double strands and exhibit significant nuclease resistance, which further facilitates in vivo administration [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The 2'-position in the ribose moiety of RNA is prime target for chemical modifications. Extensive research work is going on towards the study of structural properties, biological applications and delivery strategies of oligonucleotides-incorporated with 2'-deoxy-2'fluoronucleotide in combination with other structural modifications [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Oligonucleotides containing 2'-deoxy-2'fluoronucleosides have been synthesized for regiospecific cleavage of RNA by RNase H [67].…”
Section: Application Of Fluorinated Oligonucleotide Analoguesmentioning
confidence: 99%
“…Oligonucleotides containing 2'-deoxy-2'fluoronucleosides have been synthesized for regiospecific cleavage of RNA by RNase H [67]. Incorporation of 2'-deoxy-2'-fluoronucleotide into oligonucleotides induces substantial enhancement in their binding affinities to RNA targets [68]. Damha On the other side, very interesting and novel studies have been carried out by Erande et al using 3'-deoxy-3'ribofluoro/xylofluoro uridine incorporated oligonucleotides (2'-5'-strand) [85].…”
Section: Application Of Fluorinated Oligonucleotide Analoguesmentioning
confidence: 99%